(untitled) (Bioagro, 2024)
Tomato is an important vegetable and when grown in greenhouses its yield can be affected by the whitefly, Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae). For its control, organo-synthetic pesticides are frequently sprayed, the adverse effects of which include the development of resistance and ecological imbalances. It is necessary to evaluate some alternatives that, if effective, could be included in pest management. During July - October 2023, a trial was conducted in a 1000 m2 greenhouse arranged in three randomized blocks to evaluate the effect of three doses of azadirachtin-based insecticides (600, 800 and 1000 mL.ha-1), of the entomopathogenic fungus Beauveria bassiana (50, 100 and 150 g.ha-1) and of thiamethoxam (300, 350 and 400 g.ha-1). One untreated plot per insecticide type was included as a control for 12 treatments, which were analyzed using a 3x3 + 1 factorial design (factor A: insecticides x Factor B: dose + control) in a randomized block arrangement. The number of nymphs and the number of adults of the pest was counted, the control efficacy was calculated and the yield per ha was estimated. Results showed that azadirachtin applied at 1000 mL.ha-1 and B. bassiana sprayed at 150 g.ha-1 exhibited the lowest number of nymphs and adults (3 individuals) of T. vaporariorum, the highest control efficacy (>95%) combined with high yields (44,2-46.5 t.ha-1). Sprays of azadirachtin and B. bassiana could reduce T. vaporariorum populations and the impact of inappropriate use of organo-synthetic pesticides.